Optimization of Satreskrim Investigations to Improve the Resolution of Violent Theft Crime Cases at the Pasuruan Police - Sandypandin, Novan (Indonesian Journal of Police Studies, 2024)
This abstract aims to present a brief overview of the efforts made by the Criminal Investigation Unit (Satreskrim) in improving the resolution of violent theft cases at the Pasuruan Police Station. This research focuses on optimizing the investigation process by Satreskrim to achieve increased efficiency and effectiveness in handling these cases. The methods used include data analysis of previous cases, use of technology, capacity building of investigators, and collaboration with related agencies. The results of this study show that the optimization of investigations by Satreskrim can accelerate the resolution of cases, increase public trust in law enforcement, and reduce the crime rate of violent theft in the Pasuruan Police Area. These findings make an important contribution to the understanding of effective law enforcement strategies in dealing with criminal acts particularly in the context of violent theft.